PELANGGARAN MAXIM DALAM NOVEL ASAL KAU BAHAGIA KARYA BERNARD BATUBARA - Prapti Wigati Purwaningrum (Wanastra: Jurnal Bahasa dan Sastra, 2019)
The purposes of this study is to describe what and how the Flouts exploiting maxims of the cooperative principle in the dialogues “Asal Kau Bahagia” novel by Bernard Batubara. The approach of this study is qualitative with the content analysis method because this study prioritizes the content approach of the dialogues in the novel. The writer choses this novel because the storyline is simple, easy to understand, and lead the reader imagination especially what Radha experienced when He seemed to be losing his grip on life. In addition, in it there are many dialogues that flouts exploiting maxims of cooperative principle. This research is focused on speech which contains Flouts exploiting maxims and its implications that are adjusted based on the context in the story. Some of the theories used in this study include Implicature theory by Grice, and the principle of relevance by Sperber & Wilson. The conclusion of this study is the writer found 16 data which contained fouts exploiting maxims in cooperative principle. From these data, the most Flouts exploiting maxim of quality and quantity occurred in each of 6 data, Flouts exploiting maxim of reevance consist of 8 data, Flouts exploiting maxim of manner 3 data. Flouts exploiting maxims occur in this novel include the purposes of hiding a secret, giving an explanation, insinuating, asking for an excuse, distracting the opponent's speech, and face saving acts of the speaker and also the hearer. Keywords: Pragmatic, implicature, Flouts exploiting maxims .Asal Kau Bahagia Novel by Bernard Batubara